Analyzing Coverages of Cyber Insurance Policies Using Ontology - Charalambous, Markos; Farao, Aristeidis; Kalantzantonakis, George; Kanakakis, Panagiotis; Salamanos, Nikos; Kotsifakos, Evangelos; Froudakis, Evangellos (My University, 2022)
In an era where all the transactions, businesses and services are becoming digital and online, the data assets and the services protection are of utmost importance. Cyber-insurance companies are offering a wide range of coverages, but they also have exclusions. Customers of these companies need to be able to understand the terms and conditions of the related contracts and furthermore they need to be able to compare various offerings in order to determine the most appropriate solutions for their needs. The research in the area is very limited while at the same time the related market is growing, giving every potential solution a high value. In this paper, we propose a methodology and a prototype system that will help customers to compare contracts based on a pre-defined ontology that is describing cyber-insurance terms. After a first preliminary analysis and validation, our approach accuracy is averaging at almost 50%, giving a promising initial evaluation. Fine tuning, larger data set assessment and ontology refinement will be our next steps to improve the accuracy of our tool. Real user evaluation will follow, in order to evaluate the tool in real world cases.
Keywords: Cyber-insurance; Ontology; Coverages; Exclusions; Premium